Aega sheni, a new species of Aegidae (Crustacea: Isopoda: Cymothoida) from southern China and Australia - Yu, Haiyan; Bruce, Niel L. (Zootaxa, 2006)
Aega sheni sp. nov. from Chinese and Australian waters, is described and figured. This species is characterized by the plate-like expansion of antennule peduncle articles 1 and 2, very large eyes (nearly making contact), numerous robust setae on the inferior margins of the ischium of pereopods 2 and 3, large distal lobe on the propodus of pereopods 1–3, shape and setation of the uropods, and the rounded pleotelson posterior margin. Aega sheni has been recorded at depths of 300–435 metres.